A Comparison of Malaysian and Philippine Responses to China in the South China Sea. (16th June 2016) - Kreuzer, Peter
Abstract: The conflicts in the South China Sea have caught much attention in the past few years. The vast majority of academic studies focus almost exclusively on the Sino-Vietnamese and the Sino-Philippine conflicts in the South China Sea and the Sino-Japanese conflict in the East China Sea. By not considering the structurally fairly similar conflict between China and Malaysia and generally focusing on the past decade only those analyses neglect variation in Chinese conflict behaviour over time and between opponents. This article compares the high-profile Sino-Philippine conflict to the rather smooth relations between China and Malaysia. Whereas China has regularly challenged Philippine claims and activities in disputed regions, it has exhibited much more restraint towards Malaysia, even though the two countries' claims overlap and Malaysia, unlike the Philippines, has been extracting substantial resources (LNG) from regions disputed with China since the 1980s. I argue that much of the observable between-country and over-time variation in Chinese conflict behaviour is rooted in the approaches chosen by China's opponents for framing their overall bilateral relationships with China. Specifically, it is argued that China's opponents in territorial and maritime conflicts can assuage Chinese behaviour on the ground by signalling recognition and respect of China's overall self-role and world-order conceptions. Conversely, if they challenge the overarching Chinese self-role and world-order conceptions, China tends towards a coercive strategy. China will also tolerate higher levels of assertiveness of its opponent in the contest for sovereignty, when the opponent displays respect for China's recognition needs.